We need to use the formula to find the average rate of change between a and b:
![(f(b)-f(a))/(b-a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ahnspg2gjcutb1i0cb8uhhz0ab85k1hd43.png)
In this case, since we are asked for the average rate of change from x=-4 to x=0
![\begin{gathered} a=-4 \\ b=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r9j7930j4ja250csvojhbpcl5vqvmjr6lc.png)
Now we find f(a) which is the value of the function at a. In this case, we need f(-4):
![f(a)=f(-4)=1](https://img.qammunity.org/2023/formulas/mathematics/college/32yush77t8q3xeioth0yod3fntt1xqbp3p.png)
We do the same to find f(b), which in this case is f(0), so we look for the value of the y-axis (the function) at x=0:
![f(b)=f(0)=-1](https://img.qammunity.org/2023/formulas/mathematics/college/qk9qhia81cspfect2p0duhxlvaj6uac6jd.png)
Now we substitute in the initial formula for the average rate of change:
![undefined]()